Rational Control of Diffraction and Interference from Conformal Phase Gratings: Toward High‐Resolution 3D Nanopatterning. Issue 12 (25th September 2014) - Hyun, Jerome K.; Park, Junyong; Kim, Eunhye; Lauhon, Lincoln J.; Jeon, Seokwoo
<x xml:space="preserve">Abstract</x> The effective control of the zeroth order diffraction efficiency in phase gratings is a key technique that enables implementation of high‐performance optical elements. An interesting and unexplored application is in the field of phase mask interference lithography, which uses a conformal grating to generate periodic 3D nanopatterns by the optically formed Talbot image. A good understanding of the influence of phase and diffraction on the Talbot image is necessary for achieving rational design of 3D nanopatterns, especially in the regime where the grating periodicity is close to the wavelength and where scalar treatments fail to accurately capture the phase optics. The ability to precisely control diffraction and interference in this regime is illustrated by tuning the grating height in the phase mask up to values that exceed a full phase cycle. These results highlight a powerful degree of freedom and solid guidelines for controlling the structural resolution of optically generated 3D nanopatterns.